1999
DOI: 10.1046/j.1365-2273.1999.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma antigen in patients with cancer of the larynx

Abstract: The purpose of this study was to evaluate the clinical usefulness of squamous cell carcinoma antigen (SCC Ag) in patients with squamous cell carcinoma of the larynx. Plasma specimens were obtained from 70 patients with cancer of the larynx before and after treatment and during follow-up. Disease status and the marker levels were determined blind to each other. Microparticle enzyme immunoassay (IMx SCC) was used to measure the SCC Ag level. Applying standard normal limits the sensitivity of the marker at diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…Furthermore, the pro-invasive ability of SCC-Ag has been supported by clinical studies demonstrating positive relationships between serum SCC-Ag levels and tumor progression, lymph node metastasis, and tumor stage. [4], [13], [19], [24], [25], [26] In our study, we demonstrated that the SCC-Ag was significantly lower after treatment in OSCC (Fig. S1A).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the pro-invasive ability of SCC-Ag has been supported by clinical studies demonstrating positive relationships between serum SCC-Ag levels and tumor progression, lymph node metastasis, and tumor stage. [4], [13], [19], [24], [25], [26] In our study, we demonstrated that the SCC-Ag was significantly lower after treatment in OSCC (Fig. S1A).…”
Section: Discussionsupporting
confidence: 54%
“…24,25 One study reported that pretreatment levels of squamous cell antigen were positively associated with disease recurrence in 70 patients with laryngeal cancer, indicating a potential role as a prognostic marker, although whether this marker added to or simply reflected known prognostic factors was not evaluated. 26 We found that sVEGFR1 was neither raised in patients with HNSCC nor related to clinicopathologic or outcome measures. It therefore does not have a role as a circulating tumor or prognostic marker.…”
Section: Discussionmentioning
confidence: 97%
“…This protein was detected in our ADC and SCC pools with spectral counts of 14 and 10, respectively (supplemental Table S5). Squamous cell carcinoma antigen (SCC) is also a well-known tumor marker frequently observed in lung and laryngeal cancer patients' sera (38,39). We observed this molecule with a spectral count of 13 in the SCC pool and three in the ADC pool.…”
Section: Nsclc Shotgun Proteomic Analysis Detection Coveragementioning
confidence: 89%